Analysis on Two Fake “Topology Diagram of Mineral Paragenesis Combination in Multi-Component Open Systems” Published by Jingwen Mao, Academician of The Chinese Academy of Engineering - Han, Fa (European Journal of Applied Sciences, 2024)
The making principles and methods of "multi-component open system mineral Paragenesis combination topology diagram" are one of the most basic cutting-edge research topics in geoscience. So far, only a few professors among Chinese geologists can do this kind of work. Researcher Mao Jingwen of the Institute of Mineral Resources of the Chinese Academy of Geological Sciences published an academic paper and a doctoral thesis in 1986 and 1988 respectively, which contained two "topological diagrams of multi-component open system mineral Paragenesis combinations". We have proved through detailed research that the two diagrams produced by Mao Jingwen have the following series of fundamental errors: ①He doesn’t comply with the principle of mineral phase law (P≦C), ② He doesn’t comply with the Gibbs phase law (F=Ci+2-φ=0), ③ He doesn’t know how to determine the effective inert components and excess components (as shown in Figure 1 of the text, he replaced the effective inert components with excess components in the composition ⊿ diagram), ④ He doesn’t know how to determine the relationship between symbiotic minerals (For example, the four univariable reaction equations in Figure 2 of this article are wrong), ⑤He doesn’t know how to determine the stoichiometry of univariable reaction equations, ⑥It violates the principle of "mass conservation" before and after the univariate reaction. This fully shows that Mao Jingwen himself does not understand the principles and methods of drawing topological diagrams of mineral symbiosis combinations, that is, both diagrams are fake, and Mao Jingwen deliberately falsified them.